Albania : Background Information. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper describes a evolution of the financial system in Albania. The paper highlights that a two-tier banking system was created following passage of a new Central Bank Law and Commercial Banking Law in April 1992. The State Bank of Albania became the Bank of Albania and retained only the functions of a central bank. Its commercial operations were hived off to become the National Bank of Albania in July 1992, which was subsequently merged with the Albanian Commercial Bank to form the National Commercial Bank of Albania on January 1, 1993.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet